1999
DOI: 10.1518/001872099779577246
|View full text |Cite
|
Sign up to set email alerts
|

Human Sensitivity to Variability Information in Detection Decisions

Abstract: Three studies investigated the ability of observers to extract and use reliability information from graphical elements presented on a visual display. The first experiment assessed observers' accuracy in detecting differences in source reliability based on differences in the temporal variability of the sources. Observers' accuracy improved as the sample size and the difference in the underlying source variability increased. The second study investigated observers' efficiency in using the information about sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…In all conditions, and for both green and red warnings, participants used higher-than-optimal cutoffs that risked high miss rates. The failure to reach optimal cutoffs and the continued response to nonvalid warnings are in line with previous results that showed that participants failed to weigh information sources optimally, although they differentiated between the weights they gave to information from different sources (e.g., Montgomery, 1999;Montgomery & Sorkin, 1996).…”
Section: The Cutoff Settingssupporting
confidence: 90%
“…In all conditions, and for both green and red warnings, participants used higher-than-optimal cutoffs that risked high miss rates. The failure to reach optimal cutoffs and the continued response to nonvalid warnings are in line with previous results that showed that participants failed to weigh information sources optimally, although they differentiated between the weights they gave to information from different sources (e.g., Montgomery, 1999;Montgomery & Sorkin, 1996).…”
Section: The Cutoff Settingssupporting
confidence: 90%
“…Given these heavy demands, the failure to match the performance of the OW model is unsurprising; researchers have long recognized that limits on information and information-processing abilities place bounds on human cognition that can prevent human decision makers from reaching putatively normative performance (Simon, 1955; Tversky & Kahneman, 1974). Nonetheless, human decision makers can at least approximate the performance of a linear cue combination rule (Einhorn, Kleinmuntz, & Kleinmuntz, 1979), and although they tend not to weight cues optimally (e.g., Johnson, Cavanagh, Spooner, & Samet, 1973; Montgomery, 1999, 2001; Montgomery & Sorkin, 1996), their deviations from normative weighting are likely to have modest effects on performance (Dawes & Corrigan, 1974; Wainer, 1976). Comparing the earlier predictions of the OW and UW models, for instance, shows that an equal-weighting rule for combining human and automation judgments would have approached the performance of the optimal-weighting rule.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, human decision makers can at least approximate the performance of a linear cue combination rule (Einhorn, Kleinmuntz, & Kleinmuntz, 1979), and though they tend not to weight cues optimally (e.g., Johnson, Cavanagh, Spooner, & Samet, 1973;Montgomery, 1999Montgomery, , 2001Montgomery & Sorkin, 1996), their deviations from normative weighting are likely to have modest effects on performance (Dawes & Corrigan, 1974;Wainer, 1976). Comparing the predictions of the OW and UW models above, for instance, shows that an equal-weighting rule for combining human and automation judgments would have approached the performance of the optimal-weighting rule.…”
Section: Benchmarking Aided Decisions 35mentioning
confidence: 99%
“…Besides the media effects there are also other individual aspects, starting with the widely differing perceptive abilities (Montgomery 1999). Visual learners are better off when they are presented with graphical displays; whilst auditive learner types ought to acquire information rather acoustically (Ferrari and Sternberg 1998).…”
Section: Contents Media Learner Typesmentioning
confidence: 99%